It’s Reception all the Way Down: A Review of The Reception of Jesus in the First Three Centuries - Rollens, Sarah E. 1984- (2021)
La Réception de Jésus aux trois premiers siècles est une collection en trois volumes qui explore la réception des traditions sur Jésus. Composés de 82 essais de plus de 60 contributeurs, ces volumes examinent à la fois les expressions textuelles de l'ancien Jésus, de même que les représentations matérielles. Cet essai de synthèse observe en profondeur ces contributions importantes en : 1) discutant de l'approche méthodologique de l'ensemble du projet et en 2) examinant en détails trois exemples de chapitres.
The Reception of Jesus in the First Three Centuries is a three-volume collection that explores the reception of traditions about Jesus. Comprised of 82 essays by over 60 individual contributors, these volumes examine both textual expressions of ancient Jesus traditions, as well as material representations. This review essay looks closely at these important contributions by 1) discussing the overall project’s methodological approach and 2) examining three sample chapters in detail.
Keywords: Sculpture; réception; traditions de Jésus; Jésus; évangiles; christianisme primitif; sculptureapocalypse; Reception; Jesus traditions; Jesus; Gospel; Early Christianity; Apocalypse